Nephrolepis exaltata - Hibiscus rosa-sinensis combination herbal mask decreases levels of reactive oxygen species in nasal wash - Prasetyo, Awal; Ariani, Resti; Antari, Arlita Leniseptaria; Sadhana, Udadi; Miranti, Ika Pawitra; Kristina, Tri Nur (Universa Medicina, 2020)
BackgroundPoor air and mask quality in the work environment increase the risks of inflammation, reactive oxygen species (ROS) production, ongoing oxidative stress, and superoxide dismutase 3 (SOD3) levels in the airways. The study aimed to investigate the effect of the Nephrolepis exaltata - Hibiscus rosa-sinensis (NE-HRS) combination herbal mask on the airways, as measured by ROS and SOD3 levels in the nasal wash of textile industry workers.MethodsThis was a pre- and post-test randomized controlled trial, consisting of 30 subjects with ³5-year working time, conducted for eight weeks and monitored every ten days. Subjects were randomized into 3 groups, regular surgical mask group (n=10), NE-HRS combination herbal mask group (n=10) and factory mask group (n=10). SOD3 and ROS levels were determined using ELISA. Data were analyzed with One-way ANOVA and multiple comparison tests.Results ROS levels decreased significantly in all groups (p=0.004). Regular surgical masks decreased ROS levels by 67.90 ± 50.66 pg/mL, NE-HRS combination herbal masks by 49.91 ± 45.06 pg/mL, and factory masks by 193.96 ± 128.36 pg/ml. SOD3 levels also decreased but not significantly (p=0.053). Differences in ROS levels between surgical mask and NE-HRS combination herbal mask was not significant (p=0.796). ConclusionHerbal masks laminated with NE-HRS combination significantly reduced ROS levels among textile industry workers. NE-HRS combination herbal masks have a similar protective effect to the regular surgical mask.